The madwoman of Chaillot [videorecording (DVD)] - Forbes, Bryan, 1926-2013; Hepburn, Katharine, 1907-2003; Boyer, Charles, 1899-1978; Dauphin, Claude, 1903-1978; Chamberlain, Richard, 1935- (Archive collection., 2011)
Life is a Sunday in the park for Aurelia, a dotty Parisian countess who looks as if she stepped out of a Georges Seurat painting. But sooner or later, Aurelia had to find out about the so-called sane world and its student unrest, the bomb, even its greedy scheme to transform the City of Light into a forest of oil derricks. If this is sanity, she'll do anything to stop it! In this spirited and timelier than ever satire from Jean Giradoux's famed play.